PENGARUH MODEL PEMBELAJARAN SOMATIS AUDITORI VISUAL INTELEKTUAL (SAVI) TERHADAP MENULIS PUISI PADA SISWA KELAS VIII SMP NEGERI 35 PALEMBANG - Masnunah, Masnunah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Abstract— The purpose of this study is to determine the influence and significance level of the influence of learning model of Somatis Auditori Visual Intelektual (SAVI) on students' ability to write poetry of class VIII SMP Negeri 35 Palembang. The method used is an experimental method with quantitative data analysis techniques. Based on the result of data analysis, it is known that the result of t test of Ttable> Thitung indicates that there is significant influence, while r value of 0.638 indicates the significance level of influence of Somatis Auditori Visual Intellectual (SAVI) model to write strong poetry Keywords— Writing poetry, visual learning model of visual intellectual auditory (SAVI)